Les humanités numériques, un lieu pour les archives du bizarre - Myriam Marrache-Gouraud (Les Cahiers de l'École du Louvre)
The foundations of the Curiosithèque project are presented here: the aim is to map and inventory the written production that accompanied collections of curiosities by bringing together for the first time in a digital library the scattered volumes and fragments of a library of curiosities (1565–1750). The possible applications of the project are demonstrated using a case study drawn from the printed works in the Gaignières collection.